1992
DOI: 10.1190/1.1443332
|View full text |Cite
|
Sign up to set email alerts
|

Modeling elastic fields across irregular boundaries

Abstract: Geologists often see the earth as homogeneous blocks separated by smoothly curving boundaries. In contrast, computer modeling algorithms based on finite‐difference schemes require elastic constants to be specified on the vertices of a regular rectangular grid. How can we convert a continuous geological model into a form suitable for a finite‐difference grid? One common way is to lay the finite‐difference grid down on the continuous geological model and use whatever elastic constants happen to lie beneath each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…This means that we increase the velocity in some regions of the original model as well as decrease it in other regions of the original model. The volumetric averaging of slowness (Muir et al, 1992;Moczo et al, 2000) is the most appropriate method to discretize an isotropic model to an isotropic model.…”
Section: Discussion Of the Algorithm For A 3d Isotropic Modelmentioning
confidence: 99%
“…This means that we increase the velocity in some regions of the original model as well as decrease it in other regions of the original model. The volumetric averaging of slowness (Muir et al, 1992;Moczo et al, 2000) is the most appropriate method to discretize an isotropic model to an isotropic model.…”
Section: Discussion Of the Algorithm For A 3d Isotropic Modelmentioning
confidence: 99%
“…derived the effective properties of a finely layered medium based on this long-wavelength equivalent medium theory. In order to accurately model wave propagation through boundaries in an elastic solid with a Finite-Difference (FD) scheme, Muir et al (1992) extended Schoenberg and Muir's derivation to represent the stiffness coefficient of a grid cell traversed by a boundary. developed this idea further to represent fractures with linear slip behavior in a FD scheme.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…Based on this theory, smoothing the grid points around the interface can give second-order accuracy to approximate the boundary conditions of the interface [5]. Muir et al [34] applied the S-M calculus [40], which is a general formulation of Backus averaging [2], to compute the equivalent value of elastic parameters for the grid points near the discontinuous interfaces [34]. Their results demonstrated that the averaging method can effectively suppress the spurious diffractions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Muir et al [34] applied the S-M calculus [40], which is a general formulation of Backus averaging [2], to compute the equivalent value of elastic parameters for the grid points near the discontinuous interfaces [34]. Their results demonstrated that the averaging method can effectively suppress the spurious diffractions [34]. The idea of averaging for dealing with discontinuous interfaces has also been applied with the finite-element methods with a lumped mass matrix, which leads to an effective interface-smoothing scheme by summing the rows of the mass matrix for constant-density acoustic media [41].…”
Section: Introductionmentioning
confidence: 99%